Climate change challenges, plant science solutions - Eckardt, Nancy A.; Ainsworth, Elizabeth A.; Bahuguna, Rajeev N.; Broadley, Martin R.; Busch, Wolfgang; Carpita, Nicholas C.; Castrillo, Gabriel; Chory, Joanne; DeHaan, Lee R.; Duarte, Carlos M.; Henry, Amelia; Jagadish, S.V. Krishna; et al. (Oxford University Press, 2023)
Climate change is a defining challenge of the 21st century, and this decade is a critical time for action to mitigate the worst effects on human populations and ecosystems. Plant science can play an important role in developing crops with enhanced resilience to harsh conditions (e.g. heat, drought, salt stress, flooding, disease outbreaks) and engineering efficient carbon-capturing and carbon-sequestering plants. Here, we present examples of research being conducted in these areas and discuss challenges and open questions as a call to action for the plant science community.